Prognostic factors associated with small for gestational age babies in a tertiary care hospital of Western Nepal: A cross‐sectional study. Issue 1 (15th February 2021) - Chaudhary, Nagendra; Yadav, Shree Narayan; Kalra, Suresh Kumar; Pathak, Santosh; Gupta, Binod Kumar; Shrestha, Sandeep; Patel, Matthew; Satia, Imran; Sadhra, Steven; Bolton, Charlotte Emma; Kurmi, Om Prakash
Abstract: Background: Small for gestational age (SGA) is common among newborns in low‐income countries like Nepal and has higher immediate mortality and morbidities. Objectives: To study the prevalence and prognostic factors of SGA babies in Western Nepal. Methods: A cross‐sectional study (November 2016‐October 2017) was conducted in a tertiary care hospital in Western Nepal. Socio‐demographic, lifestyle factors including diet, and exposures including smoking and household air pollution in mothers who delivered newborns appropriate for gestational age (AGA), SGA and large for gestational age (LGA) were recorded. Logistic regression was carried out to find the odds ratio of prognostic factors after adjusting for potential confounders. Results: Out of 4000 delivered babies, 77% (n = 3078) were AGA, 20.3% (n = 813) were SGA and 2.7% (n = 109) were LGA. The proportion of female‐SGA was greater in comparison to male‐SGA (n = 427, 52.5% vs n = 386, 47.5%). SGA babies were born to mothers who had term, preterm, and postterm delivery in the following proportions 70.1%, 19.3%, and 10.6%, respectively. The average weight gain (mean ± SD) by mothers in AGA pregnancies was 10.3 ± 2.4 kg, whereas in SGA were 9.3 ± 2.4 kg. In addition to low socioeconomic status (OR 1.9, 95% CI 1.1, 3.2), other prognostic factors associated with SGA were lifestyle factors such as low maternal sleep duration (OR 5.1, CI 3.6, 7.4) and monthly or less frequent meat intake (OR 5.0, CI 3.2, 7.8). Besides smoking (OR 8.8, CI 2.1, 36.3), the other major environmental factor associated with SGA was exposure to household air pollution (OR 5.4, 4.1, 6.9) during pregnancy. Similarly, some of the adverse health conditions associated with a significantly higher risk of SGA were anemia, oligohydramnios, and gestational diabetes. Conclusions: SGA is common in Western Nepal and associated with several modifiable prognostic factors.